Development of patient-specific drug-releasing round window implants for the treatment of inner ear diseases (Transactions on Additive Manufacturing Meets Medicine, 2019)
Motivation: The modern therapy of inner ear disorders is increasingly being determined by pharmacological therapies and local delivery of drugs to the inner ear. But local drug delivery to the inner ear is very challenging. Access to the inner ear is usually found via the natural membrane structure of the round window membrane (RWM). The RWM lies in a bony round window niche (RWN), which allows to deposit drugs here. The problem now is that this niche is shaped individually very different and optimally drug loading has to be ensured.Material/Methods: The individual anatomical structures of the RWN of the patients are determined by segmentation of cone beam computed tomography (CBCT) imaging of the RWN of 50 temporal bones. Different partners using varying additive manufacturing processes will develop individualised biodegradable drug implants. The additive manufacturing processes could be Fused Deposition Modeling, Digital Light Processing, Two-Photon-Polymerisation and Micro Injection Molding. This implants will be 3D printed directly in the operating room after automatic segmentation of individual anatomies of the RWN. And then the individualised implants will be inserted into the patients RWN in a small intervention.Results/Discussion: Due to the large individual anatomical variability of the RWN one new approach that offers the potential for non invasive local delivery to the inner ear is by developing a 3D printed, patient individualised, biodegradable drug implant that fits exactly into the RWN. This implant keeps the drug in place for a few weeks to get a much more dwell time and keep the drug delivery time extended.